Shaping Sustainable Practices: A Community-Based Social Marketing Perspective on Consumers and Entrepreneurs - Pranatasari, Fransisca Desiana; Diva, Maria Angela; Ismawati, Anastasia Filiana; Sundari, Sun Sun (Review of Management and Entrepreneurship, 2025)
Global issues regarding environmental sustainability concerns and irresponsible consumption are now increasingly echoed. Therefore, this research is very important, to provide urgent solutions towards sustainable development. Both from the consumer and producer sides, they should gradually start to change their attitudes and consumption behaviors. The challenge is the lack of awareness or priority for environmentally friendly products to obstacles in the adoption of sustainable products. Therefore, better education and increased accessibility of environmentally friendly products are needed to encourage wider community participation, one of which is through the community. This study aims to explore the role of community-based social marketing so that they can shape lifestyles in accordance with sustainable practices. For this purpose, data was collected using a qualitative approach with interview, observation, and documentation data collection techniques on 20 key informants through convenience sampling, namely those who are actively involved in the community campaigning for a sustainable lifestyle, both community managers, entrepreneurs, and consumers themselves. The data is analyzed using content analysis. The results of this study show that social interaction in the context of community-based social marketing with other traditional markets. Community commitment encourages consumers & entrepreneurs to behave sustainably. These community norms and community identities influence sustainable behavior. Sustainable practices for entrepreneurs are more inclined towards tripple bottom line applications and for consumers are more inclined to more meaningful consumption applications. Furthermore, collaboration is also needed to really form a wider ecosystem in the context of massive synergy of sustainable lifestyles.